AN ANALYSIS ON SOCIO-ECONOMIC STATUS OF SCHEDULED CASTES POPULATION IN TIROL VILLAGE, ARAMBAGH, HOOGHLY - Sardar, Sanjib (International Journal of Research -GRANTHAALAYAH, 2020)
The present paper is concerned with Socio-Economic background of Scheduled Castes (SCs) population in Tirol village, Arambagh and its major focus is to analyze the main obstacles on the way to socio-economic development. The basic information has been collected through the well-prepared questionnaire and supplemented by relevant secondary data. An intensive study was run over 287 sample household and the result was shown in the tabulated form. The outcome of the study reveals that 88.88 percentage sample population belong to SCs community and the percentage of men and women is 49.64 and 50.36 respectively. The educational level of the study area is not so good among the people of SCs community except the present generation and in terms of higher education the level is very poor. The rate of literacy among women is far behind than men although the number of women is more than men. The monthly income of SCs is not up to the mark. A large number of people of the SCs community are unemployed and the main economic activities are based on agriculture. They usually live in mud house, although there are several concrete houses built with the help of Indira Awas Yojana. So as a whole it is observed from the present study that, the socio-economic condition of SC community is poor and Government should pay attention to socio-economic backwardness and find requisite steps for sustainable development.